The Title System of Pingelap and the Diversity of Atoll Political Organizations - Damas, David (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1983)
This paper focuses on the factors involved in the development, political process, and guiding principles of a title system which formed the basis of polity on Pingelap atoll in the Eastern Carolines. The evolution of the system of titles is discussed with particular attention to the historical and geographical factors involved in its development, and the effects of contact with other cultures on that system. Comparisons are drawn within Micronesia and used to create a base for broader examination of Pacific polities.